Wet‐Spinning of Biocompatible Core–Shell Polyelectrolyte Complex Fibers for Tissue Engineering. Issue 23 (19th October 2020) - Cui, Qing; Bell, Daniel Josef; Rauer, Sebastian Bernhard; Wessling, Matthias
Abstract: Polyelectrolyte complex fibers (PEC fibers) have great potential with regard to biomedical applications as they can be fabricated from biocompatible and water‐soluble polyelectrolytes under mild process conditions. The present publication describes a novel method for the continuous fabrication of PEC fibers in a water‐based wet‐spinning process by interfacial complexation within a core–shell spinneret. This process combines the robustness and flexibility of nonsolvent‐induced phase separation (NIPS) spinning processes conventionally used in the membrane industry with the complexation between oppositely charged polyelectrolytes. The produced fibers demonstrate a core–shell structure with a low‐density core and a highly porous polyelectrolyte complex shell of ≈800 μm diameter. In the case of chitosan and polystyrene sulfonate (PSS), mechanical fiber properties could be enhanced by doping the PSS with poly(ethylene oxide) (PEO). The resulting CHI/PSS‐PEO fibers present a Young modulus of 3.78 GPa and a tensile strength of 165 MPa, which is an excellent combination of elongation at break and break stress compared to literature. The suitability of the CHI/PSS‐PEO fibers as a scaffold for cell culture applications is verified by a four‐day cultivation of human HeLa cells on PEO‐reinforced fibers with a subsequent analysis of cell viability by fluorescence‐based live/dead assay. Abstract : Core–shell polyelectrolyte fibers are synthesized via polyelectrolyte complexation of chitosan (CHI) and polystyrene sulfonate (PSS) within a 3D‐printed nozzle. This continuous water‐based process yields fibers with an excellent combination of elasticity and break stress. Polyelectrolyte fibers prove to be suitable as scaffold for the cultivation of cells with high cell viability, leading to well adhering tissue‐like cell layers.